Original sin [videorecording (DVD)] - James, P. D.; Marsden, Roy, 1941-; Benson, Andrew; Grieve, Andrew; Bannen, Ian, 1928-1999; James, P. D. (P.D. James the essential collection, 2008)
"Book publishing has always been a competitive business. At Peverell Press, it's becoming cutthroat"--Koch Entertainment booklet.